2010
DOI: 10.1007/s10533-010-9444-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell-wall polysaccharides play an important role in decay resistance of Sphagnum and actively depressed decomposition in vitro

Abstract: Sphagnum-dominated peatlands head the list of ecosystems with the largest known reservoirs of organic carbon (C). The bulk of this C is stored in decomposition-resistant litter of one bryophyte genus: Sphagnum. Understanding how Sphagnum litter chemistry controls C mineralization is essential for understanding potential interactions between environmental changes and C mineralization in peatlands. We aimed to separate the effects of phenolics from structural polysaccharides on decay of Sphagnum. We measured aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 42 publications
5
113
0
Order By: Relevance
“…Since both carbohydrates (Turetsky et al 2008), notably sphagnan (Painter 1991;Børsheim et al 2001;Painter 2003;Hájek et al 2011), as well as insoluble phenolics (Tsuneda et al 2001) and soluble phenolics (Freeman et al 2001;Bragazza et al 2006) have been suggested as determinants for decay resistance of Sphagnum, it would be possible to envisage that species allocate carbon to production of either primary or secondary metabolites, i.e. carbohydrates or phenolics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since both carbohydrates (Turetsky et al 2008), notably sphagnan (Painter 1991;Børsheim et al 2001;Painter 2003;Hájek et al 2011), as well as insoluble phenolics (Tsuneda et al 2001) and soluble phenolics (Freeman et al 2001;Bragazza et al 2006) have been suggested as determinants for decay resistance of Sphagnum, it would be possible to envisage that species allocate carbon to production of either primary or secondary metabolites, i.e. carbohydrates or phenolics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to true lignin, the lignin-like phenolics in Sphagnum are thought to shield the polysaccharides by forming an amorphous coat on the cell wall surface (Tsuneda et al 2001). Removal of polymeric phenolics from the litter did not substantially increase the rate of Sphagnum decomposition in vitro (Hájek et al 2011); however, their concentration seems to correlate with Sphagnum decomposability in the field (Turetsky et al 2008;Hájek et al 2011). Some studies found structural, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the growing season, days with high daily NEE were associated with increased emissions of CH 4 . The peat at this study site is primarily composed of Sphagnum moss which decomposes slowly (Hajek et al, 2011;Turetsky et al, 2008a;van Breemen, 1995). However, during the summer months, plant productivity increases considerably as daily NEE increases to −7.7 g m −2 d −1 .…”
Section: Substrate Qualitymentioning
confidence: 96%